2022
DOI: 10.1007/978-3-030-91971-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Migration: An Introduction

Abstract: Why has it been important to incorporate gender relations into our understanding of migration processes and to engender migration research? The need to do so does not only stem from the fact that women globally make up just under half of international migrants. Gender is one of the key forms of differentiation within societies which interacts with other social divisions such as age, class, ethnicity, nationality, race, disability and sexual orientation. The drivers of migration impact on women and men differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
1
6
0
3
Order By: Relevance
“…Around a third of the participants in Study 1 reported being overwhelmed by gender expectations, which led them to have a lower perception of understanding and belonging concerning their parents/family in Portugal. This fits in with the importance of considering the intersectionality between gender and migratory status, which can influence the well-being of migrant women (Christou and Kofman 2022).…”
Section: Norms and Values In Light Of Integrationsupporting
confidence: 68%
See 1 more Smart Citation
“…Around a third of the participants in Study 1 reported being overwhelmed by gender expectations, which led them to have a lower perception of understanding and belonging concerning their parents/family in Portugal. This fits in with the importance of considering the intersectionality between gender and migratory status, which can influence the well-being of migrant women (Christou and Kofman 2022).…”
Section: Norms and Values In Light Of Integrationsupporting
confidence: 68%
“…Although we cannot make a comparison between behaviors in the sample, it is worth noting that in both studies (1 and 2), the female participants emphasized the importance of affection and emotional care, while the men tended to emphasize the functional side of support. Although this study does not have a representative sample, we are interested in reflecting on these data in the light of migration theories that emphasize gender as a variable that can change the type of presence/connection that is perceived (e.g., Santos et al 2024) or even the need for visibility in terms of female migration since care is circular and intersectional (Christou and Kofman 2022).…”
Section: Affection and Dynamics Between The Digital And The Face-to-facementioning
confidence: 99%
“…In parallel with the growing feminisation of migration flows, there is an increasing interest in the issue of gender in migration studies, and this variable also becomes part of the theoretical framework for transnational families (Christou and Kofman, 2022). In these cases, researchers deal with transnational motherhood, which focuses on possible changes and adjustments in the economic sphere, the responsibilities of circular care and solidarity and family welfare (Matei and Bobârnat, 2022).…”
Section: Care Workers: Between Migration and Transnationalismmentioning
confidence: 99%
“…Unfortunately, the availability of harmonized aggregated migration data is scarce. Recently, there has been a growing emphasis on the importance of collecting sex-disaggregated data to better understand vulnerabilities, mobilities, and gender-specific outcomes, and to inform genderresponsive policy-making (Kofman, 2019;Christou & Kofman, 2022;Hennebry, KC, & Williams, 2021). Multiple studies, including those by Morokvasic (1984); Donato and Gabaccia (2015); Zlotnik (1995), have contributed to this focus on female migrants, while a separate body of literature has emerged that examines and compares the migration patterns of both female and male migrants.…”
Section: What Are the Differences In Labor Market Discrimination Base...mentioning
confidence: 99%
“…Several works have aimed to synthesize the research on gender and migration, including those by Chant (1992); Donato and Gabaccia (2015), and more recently, Christou and Kofman (2022). Changes in sex compositions of migration flows to the US using data has been analysed in the work of Katharine Donato and Donna Gabaccia's (Donato & Gabaccia, 2015).…”
Section: Introductionmentioning
confidence: 99%